In vitro germination, callus induction and phenolic compounds contents from Pyrostegia venusta (Ker Gawl.) Miers - Karina de Queiroz Braga; Mairon César Coimbra; Ana Hortência Fonsêca Castro (Acta Scientiarum. Biological Sciences, 2015)
A protocol for the in vitro germination and callus induction in Pyrostegia venusta, a medicinal plant species from the Brazilian savannah (Cerrado) is provided. The establishment of cultures of P. venusta was originally obtained from seeds germinated in vitro and induced callus directly from leaf explants of seedlings. Seeds were germinated on MS and WPM media containing 100 and 50% of salt concentration, supplemented with 30 g L-1 sucrose. Callus induction consisted of the inoculation of leaf segments on MS medium plus 2,4-D or BAP in the presence or absence of light. The germination percentage averaged 85% and the aerial parts and roots of seedlings obtained in WPM with 50 and 100% of salt concentration showed elevated contents of total phenolic compounds and flavonoids compared to those obtained on MS medium. Calli induced with lower concentrations of 2,4-D had higher fresh and dry weight values. All treatments resulted in obtaining calli with contents of total phenolic compounds and flavonoids at or above the initial explant, highlighting treatments containing 9.05 mM 2,4-D and 8.88 mM BAP in the presence and absence of light, and 17.75 mM BAP in the absence of light.